Niemann-Pick disease type C presenting as very early onset inflammatory bowel disease. Issue 7 (27th July 2019) - Dike, Chinenye Rebecca; Bernat, John; Bishop, Warren; DeGeeter, Catherine
Abstract : Niemann-Pick disease type C (NPC) has been reported in association with inflammatory bowel disease. In cases where colitis has been reported in association with NPC, the neurological manifestations of NPC often precede the development of colitis. We report a rare case of a child who presented at age 2 with perianal Crohn's disease. Initial imaging studies to characterise the disease revealed an incidental finding of splenomegaly. Extensive workup for splenomegaly revealed NPC1 mutations consistent with NPC disease. He did not have any typical neurological symptoms at the time of his diagnosis. He is currently doing well on biweekly adalimumab injections for his Crohn's disease and biweekly intrathecal injections of 2-hydroxypropyl-β-cyclodextrin (VTS-270) for the NPC.